First report on mass aggregation of opiliones in China - A. Mukherjee; B. Wilske; C. Jin (Journal of Threatened Taxa, 2010)
Gregariousness is a widespread behavior among harvestmen, with reports for species from South and North America, Europe and India. The present note reports an enormous aggregation (300,000 individuals) of the harvestman Pseudogagrella sp. (Sclerosomatidae: Gagrellinae) in the tropical rain forest of Xishuangbanna, southern prefecture of Yunnan Province, China. The aggregation was found during winter months, from November to March, in five adjacent, but clearly defined patches ranging from 1 to 6 m2. Females comprised the greater part of the aggregation and only a few males were found in the patches. With the rise in temperature, the density of individuals reduced considerably, and most of them accumulated in a single patch and finally disappeared by the end of April